Mycoplasma genitalium infection in the female reproductive system: Diseases and treatment - Yu, Jianwei; Zhou, Yan; Luo, Haodang; Su, Xiaoling; Gan, Tian; Wang, Jingyun; Ye, Zufeng; Deng, Zhongliang; He, Jun (Frontiers in Microbiology, 2023)
Mycoplasma genitalium is a newly emerged sexually transmitted disease pathogen and an independent risk factor for female cervicitis and pelvic inflammatory disease. The clinical symptoms caused by M. genitalium infection are mild and easily ignored. If left untreated, M. genitalium can grow along the reproductive tract and cause salpingitis, leading to infertility and ectopic pregnancy. Additionally, M. genitalium infection in late pregnancy can increase the incidence of preterm birth. M. genitalium infections are often accompanied by co-infection with other sexually transmitted pathogens (Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis) and viral infections (Human Papilloma Virus and Human Immunodeficiency Virus). A recent study suggested that M. genitalium plays a role in tumor development in the female reproductive system. However, few studies endorsed this finding. In recent years, M. genitalium has evolved into a new “superbug” due to the emergence of macrolide- and fluoroquinolone-resistant strains leading to frequent therapy failures. This review summarizes the pathogenic characteristics of M. genitalium and the female reproductive diseases caused by M. genitalium (cervicitis, pelvic inflammatory disease, ectopic pregnancy, infertility, premature birth, co-infection, reproductive tumors, etc.), as well as its relationship with reproductive tumors and clinical treatment.